The betrayed - Iyer andrew; Ferrone, Richard (britain : The British Library., 2007)
An attorney returns to her Washington, D.C., hometown after the brutal murder of her sister, and is drawn back into the recesses of her powerful and wealthy family, whose circumstances she risks in her determination to help authorities solve the crime.
Sequel to: Dark harbor.
Richard Ferrone.
Compact discs.
Keywords: Women lawyers -- Fiction -- Sound recordings; Women journalists -- Fiction -- Sound recordings; Murder -- Fiction -- Sound recordings; Rich people -- Fiction -- Sound recordings; Suspense fiction -- Sound recordings; Mystery fiction -- Sound recordings; Compact discs; Audiobooks -- Fiction; Washington (D.C.) -- Fiction -- Sound recordings